Direct oral anticoagulants or vitamin K antagonists after TAVR: A systematic review and meta-analysis. (15th October 2022) - Oliveri, Federico; Montalto, Claudio; Tua, Lorenzo; Lanzillo, Giuseppe; Compagnoni, Sara; Fasolino, Alessandro; Gentile, Francesca Romana; Ferlini, Marco; Pepe, Antonella; Oltrona Visconti, Luigi; Bongiorno, Andrea; Leonardi, Sergio
Abstract: Background: Several patients undergoing transcatheter aortic valve replacement (TAVR) also require oral anticoagulation (OAC) for atrial fibrillation (AF) or deep vein thromboembolism. However, the optimal type of OAC strategy (direct oral anticoagulants, DOACs, or vitamin K antagonists, VKA) is still unclear in this setting. Method: We performed systematic literature research and meta-analysis in PubMed, Medline, and EMBASE databases for studies reporting either all-cause mortality, major/life-threatening bleeding or stroke events. Results: Ten observational studies and two randomized controlled trials (RCTs) including a total of 29, 485 patients were eligible for inclusion. Compared to VKA, DOACs use after TAVR was associated with a modest but significantly lower rates of all-cause mortality (RR 0.90; 95% CI: 0.81–0.99, p -value 0.04) with results mainly driven by observational studies. Cardiovascular mortality (RR 1.03; 95% CI: 0.81–1.30; p -value 0.84), total stroke events (RR 0.97; 95% CI: 0.76–1.23, p -value 0.79), major/life-threatening bleeding (RR 0.93; 95% CI: 0.72–1.21, p-value 0.61) and minor bleeding (RR 0.96; 95% CI: 0.74–1.23; p-value 0.72) were similar between VKA and DOACs. Conclusion: Considering the totality of available evidence, in patients who underwent TAVR with a concomitant indication for OAC, DOACs-based strategy is an effective and safe anticoagulation strategy compared to VKA. Highlights: Several patients undergoing TAVR have a concomitant indication for oral anticoagulation. The optimal anticoagulation strategy (DOAC or VKA) in TAVR patients with a concomitant indication for OAC is unclear. DOACs represent an effective and safe anticoagulation strategy after TAVR in patients requiring OAC.